Makna Warna pada Shio sebagai Implikasi Objek Karya Seni Lukis - Raphael Tan, Joseph; Gulendra, I Wayan; Supriyatini, Sri (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2022)
Myth is not fictional like novels that is read every day, however a reality that is believed to have happened and continues to contribute to human life and destiny. Likewise with the myths that exist in the sub-ethnic groups in the world, namely the Chinese. Chinese tribes in the world have various kinds of myths that are consciously embedded in human life. One of the most trusted is about the Chinese zodiacs. In everyday life, the majority of Chinese people believe in and adhere to the Chinese zodiac in all decisions that must be made. Shio is often used in calculating a person's luck in a year, to determine a person's name, to choose a wedding or funeral date and to read a person's character. Not infrequently, often zodiac signs are also used as a benchmark to determine the